PENGEMBANGAN UMKM BAWANG NENG AYU DI DESA CIKASO MELALUI ASPEK MARKETING, OPERATIONAL, DAN FINANCE DALAM UPAYA PENINGKATAN PENDAPATAN USAHA - Clarisa Clarisa; Emmanuel Wisnu Prayoga; Eunike Hana; Jason Valentino; Najwa Gustavi; Syahira Athayarose; Vallen Angelia; Vincent Marcello (Indonesian Collaboration Journal of Community Services, 2023)
This Community Development activity intends to provide support for MSMEs (Micro, Small and Medium Enterprises) in Kuningan Regency, one of which is 'Bawang Neng Ayu' which sells fried onion products so that they can experience an improvement in their business through the classification of business divisions based on marketing, operational, and financial. Through these activities, it is known that the owner of the 'Bawang Neng Ayu' business has a desire to develop his business so that he can follow trends, be recognized by many people and have maximum income. The research process for this activity starts from planning business development strategies to partner assistance on an ongoing basis. Through partner business assistance that has been carried out, it was found that every aspect, both marketing, operational and financial has become more optimal than before. Therefore, the hope of this activity is that partners can be helped so that their business will be more advanced in the future